Active smoking and secondhand smoke increase breast cancer risk: the report of the Canadian Expert Panel on Tobacco Smoke and Breast Cancer Risk (2009). Issue 1 (8th December 2010) - Johnson, Kenneth C; Miller, Anthony B; Collishaw, Neil E; Palmer, Julie R; Hammond, S Katharine; Salmon, Andrew G; Cantor, Kenneth P; Miller, Mark D; Boyd, Norman F; Millar, John; Turcotte, Fernand
Abstract : Four authoritative reviews of active smoking and breast cancer have been published since 2000, but only one considered data after 2002 and conclusions varied. Three reviews of secondhand smoke (SHS) and breast cancer (2004–2006) each came to different conclusions. With 30 new studies since 2002, further review was deemed desirable. An Expert Panel was convened by four Canadian agencies, the Ontario Tobacco Research Unit, the Public Health Agency of Canada, Physicians for a Smoke-Free Canada and the Canadian Partnership Against Cancer to comprehensively examine the weight of evidence from epidemiological and toxicological studies and understanding of biological mechanisms regarding the relationship between tobacco smoke and breast cancer. This article summarises the panel's full report (http://www.otru.org/pdf/special/expert_panel_tobacco_breast_cancer.pdf ). There are 20 known or suspected mammary carcinogens in tobacco smoke, and recognised biological mechanisms that explain how exposure to these carcinogens could lead to breast cancer. Results from the nine cohort studies reporting exposure metrics more detailed than ever/never and ex/current smoker show that early age of smoking commencement, higher pack-years and longer duration of smoking increase breast cancer risk 15% to 40%. Three meta-analyses report 35% to 50% increases in breast cancer risk for long-term smokers with N -acetyltransferase 2 gene ( NAT2 ) slow acetylation genotypes. The active smoking evidence bolsters support for three meta-analyses that each reported about a 65% increase in premenopausal breast cancer risk among never smokers exposed to SHS. The Panel concluded that: 1) the association between active smoking and breast cancer is consistent with causality and 2) the association between SHS and breast cancer among younger, primarily premenopausal women who have never smoked is consistent with causality.